The scapegoat in furrysuit: Fandom hierarchies as exemplified by the status of the furry fandom - Sutkowska, Agata (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
The following article attempts to demonstrate how fandoms can be regarded as communities which – despite the initial diagnosis and findings of scholars – are based on prestige social hierarchies dependent on several factors. By analyzing the case of the furry fandom (a subculture revolving around anthropomorphic animal characters), which appears to occupy a lowly position in the aforementioned hierarchy, the author discusses the selected factors, with particular emphasis on the normativity of expression in the context of mainstream patriarchal culture permeating most fandoms.